2010–2015: How have conventional descriptive analysis methods really been used? A systematic review of publications. (January 2019) - Lestringant, Pauline; Delarue, Julien; Heymann, Hildegarde
Highlights: Generic and Quantitative Descriptive Analysis were the most used for sensory profiling. Development studies correctly mirrored applications on most criteria. Choice of products in development studies did not quite reflect applications. Little methodological research was conducted on conventional descriptive analysis in 2010–2015. Abstract: Conventional descriptive analysis (DA) has been widely applied to describe the sensory characteristics of products. An analysis of the scientific literature was performed to better understand the context in which descriptive methods are utilized. When DA is used in methodological research, either to test the method itself, or to compare to new methods, is that representative of its use in application studies aiming at obtaining sensory descriptions? Web of Science was queried using "sensory profile" and "descriptive analysis" as search terms from 2010 to 2015. For each generated result, the following metadata were extracted: number and type of products, number of panelists, training and evaluation methods, and data analysis. The data were analyzed according to the goals of the study (using or developing sensory methods) and type of journal publishing the article (sensory specific journal or other). Out of 360 selected entries using DA, 20 used DA in conjunction with rapid methods, and 5 with temporal methods. 93% of DA experiments were used to obtain information about products in non-sensory specific journals. Alcoholic beverages, produce, and dairy were the top 3 categories assessed. Some product categories, such as starches and condiments/oil were only represented in application studies. Some results thus suggest a discrepancy in context between experiments designed to test methodological aspects of DA or new methods, or to obtain sensory information. Context of use should be considered when testing new methods.